The Proposed Modified Liu System with Fractional Order - Alireza K. Golmankhaneh; Roohiyeh Arefi; Dumitru Baleanu (Advances in Mathematical Physics)
The chaos in a new system with order 3 is studied. We have shown that this chaotic system again will be chaotic when the order of system is less than 3. Generalized Adams-Bashforth algorithm has been used for investigating in stability of fixed points and existence of chaos.